The book of a hundred hands : poems - Swensen, Cole, 1955- (Kuhl House poets., 2005)
The hand is second only to language in defining the human being, and its constant presence makes it a ready reminder of our humanity, with all its privileges and obligations. In this dazzling collection, Cole Swensen explores the hand from any angle approachable by language and art. Her hope: to exhaust the hand as subject matter; her joy: the fact that she couldn't. These short poems reveal the hand from a hundred different perspectives. Incorporating sign language, drawing manuals, paintings from the 14th to the 20th century, shadow puppets, imagined histories, positions (the "han.